The Odd-Even Effect in The Boards of Commissioners and Corporate Values - Islamudin, Ardhi; Wurintara, Gerrinko Giffari; Bernawati, Yustrida (Jurnal Ilmiah Akuntansi dan Bisnis, 2020)
This article expands the understanding of board of commissioners' characteristics by introducing the concept of the odd-even effect in their structure. The study employs a quantitative research approach to explore this phenomenon. When a board of commissioners is composed of an odd number of members, the decision-making process tends to be more straightforward and efficient due to the absence of tie votes, leading to a more unified perspective. In contrast, an even-numbered board is prone to voting ties, which can introduce diverse viewpoints and potential conflicts in decision-making. Consequently, the composition of the board, whether odd or even, significantly impacts corporate value. Boards with fewer members tend to be more effective, with companies having odd-numbered boards generally exhibiting higher corporate value compared to those with even-numbered boards. Keywords:    corporate value, odd-even effects, board of commissioners.